Chromatin Immunoprecipitation (ChIP) for Analysis of Histone Modifications and Chromatin-Associated Proteins - Milne, Thomas A. (2009)
Disruption of epigenetic regulators of transcription is a central mechanism of oncogenesis. Many of the advances in the understanding of these mechanisms are attributable to the successful development of chromatin immunoprecipitation (ChIP) for in vivo detection of histone modifications as well as chromatin binding regulatory proteins. This is a powerful technique for analyzing histone modifications as well as binding sites for proteins that bind either directly or indirectly to DNA. Here we present two ChIP protocols. The first is particularly useful for identifying histone modifications or binding at specific, known genomic sites. The second, employing serial analysis of gene expression, is particularly powerful for the discovery of previously unidentified sites of modification or binding.